Consumption of prebiotic sources significantly affects children’s height in a stunting locus village in Bogor Regency, Indonesia - Nadiyah, Nadiyah; Sari, Intan Permata; Dewanti, Lintang Purwara; Azra, Jeallyza Muthia; Ronitawati, Putri (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
ABSTRACTBackground: 1Stunting is a condition of growth failure in children due to chronic nutrient deficiencies for a long time, especially during the first 1000 days of life. The results of the Indonesian Nutrition Status Survey (SSGI) also showed a decrease in the stunting rate from 27.7% in 2019 to 21.6% in 2023. The 2022 SSGI data recorded that 18.7% of children in Bogor Regency were still stunted. The current reduction in stunting is still far from the target of the 2020-2024 National Medium-Term Development Plan, where the number of stunted children in Indonesia is only 14%. Children are classified as stunted if the length/height z-score-for-age is <-2 SD. Stunting can occur due to poor gastrointestinal conditions. Prebiotics and probiotics play an important role in helping to maintain gastrointestinal health. Objective: The purpose of this study was to analyze the relationship between the consumption of prebiotic and probiotic food sources and the z-score of height/length for age. Materials and Methods: This cross-sectional study included 100 children aged 6-59 months in the stunting locus village of Bogor Regency. Height/length data were obtained using a stadiometer and infantometer. Assessment of food consumption of prebiotic and probiotic sources was conducted through interviews using the Semi Quantitative-Food Frequency Questionnaire form. Bivariate test used Pearson correlation test and multivariate test used multiple linear regression test.Results: The data showed that 48% of children were stunted, and 52% were normal. Bivariate test showed correlations of food consumption of prebiotic sources (r =0.274, p=0.006) and probiotics (r=0.264, p=0.008) with height/length z-score. Multivariate test results showed that consumption of prebiotic sources influenced length/height z-score for age (β=0.007, 95%CI: 0.002-0.011, p=0.003). Conclusion: Consumption of prebiotic food sources in children can improve the z-score of height-for-age.Keywords : Consumption; height; probiotics; prebiotics; stunting